2007
DOI: 10.1110/ps.072954607
|View full text |Cite
|
Sign up to set email alerts
|

The dominant‐negative effect of the Q218K variant of the prion protein does not require protein X

Abstract: Previous studies identified several single-point mutants of the prion protein that displayed dominantnegative effects on prion replication. The dominant-negative effect was assumed to be mediated by protein X, an as-yet-unknown cellular cofactor that is believed to be essential for prion replication. To gain insight into the mechanism that underlies the dominant-negative phenomena, we evaluated the effect of the Q218K variant of full-length recombinant prion protein (Q218K rPrP), one of the dominant-negative m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 21 publications
1
37
0
Order By: Relevance
“…The human K 219 -PrP C allele (homologous to the codon 222 allele in goat PrP C ) was reported to protect humans against Creutzfeldt-Jakob disease (42), while the equivalent K 218 variant of mouse PrP C significantly reduced the fibril aggregation kinetics and generated non-proteinase K-resistant PrP (43). A plausible explanation for this inhibitory effect could be the insertion of an additional positive charge at codon 222, provided by the lysine amino acid (K), thus interfering with the PrP C -PrP Sc interaction and resulting in abolished or low conversion rates of PrP Sc (44).…”
Section: Discussionmentioning
confidence: 99%
“…The human K 219 -PrP C allele (homologous to the codon 222 allele in goat PrP C ) was reported to protect humans against Creutzfeldt-Jakob disease (42), while the equivalent K 218 variant of mouse PrP C significantly reduced the fibril aggregation kinetics and generated non-proteinase K-resistant PrP (43). A plausible explanation for this inhibitory effect could be the insertion of an additional positive charge at codon 222, provided by the lysine amino acid (K), thus interfering with the PrP C -PrP Sc interaction and resulting in abolished or low conversion rates of PrP Sc (44).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these point mutations, short deletions within the central region of the protein (⌬112-119, ⌬114 -121, and ⌬105-125) led to a dominant-negative effect in infected cells and mice, respectively (42,54). In vitro conversion reactions showed that the dominant-negative effect of point mutations at residues 218 or 171 does not require the presence of auxiliary molecules (55,56), implying a direct interaction between the C terminus of PrP and the PrP Sc seed. Collectively, these results demonstrate that modifications in the C-terminal half of the protein (after 111) can significantly impact the generation of PK-resistant PrP.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in either case, expression of dominant-negative mutants skews the competition between aggregate assembly and disassembly pathways toward the latter, allowing the effective clearance of an established prion conformer in vivo proposed for a Q172R variant, conversion of wild-type PrP, depending on their affinities for one another. 125,126 Potentially supporting this affinity-based model, PrP dominant-negative mutants differ in their effective inhibitory ratios relative to wild-type protein, 111,[125][126][127][128][129] but the same observation is also consistent with a model in which these mutants target different events in prion propagation in vivo. According to this latter idea, mutants that act at the templating surface would be effective at lower doses than those affecting fragmentation, which occurs along the length of the aggregate.…”
Section: Balancing Aggregate Assembly and Disassembly Pathwaysmentioning
confidence: 76%
“…28,117,125,135 In contrast, PrP Q219K, like, Sup35 G58D, converts to the prion conformer efficiently, destabilizes aggregates and is incompatible only with prion variants of reduced thermodynamic stability. 28,105,117,125,126 Thus, despite the distinct cellular environments in which mammalian and yeast prions propagate, the pathways of dominant inhibition that we have uncovered for Sup35 mutants may be applicable to PrP mutants and may provide mechanistic insight into the phenotypic outcomes of prion infections in that system.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
See 1 more Smart Citation